Análise da dependência térmica da germinação de braquiarão utilizando o modelo tempo térmico - Nakao, E. A. [UNESP]; Cardoso, V. J.M. [UNESP] (FapUNIFESP (SciELO), 2016)
This paper analyzed the thermal dependence on the germination of Urochloa brizantha (Stapf) Webster seeds under constant and fluctuating temperatures through the thermal time model. Germination tests were carried out at constant temperatures ranging from 8 °C to 41.5 °C in order to determine the model parameters: base (Tb), optimal (To) and maximum temperature (Tc) for germination; and the thermal time (θT) required for individual seeds to germinate. Braquiarao seeds germinate within a temperature interval from 8 °C to 41.5 °C, with an optimum range for germination estimated at 31.5 ° ≤ T ≤ 34.5 °C. Actual and expected distributions of cumulative germination percentages of U. brizantha seeds put to germinate both under controlled and uncontrolled temperature regimes were compared, and it can be seen that the model described relatively well the germination at isothermal assays; however the model failed to predict germination at a wide range of thermal fluctuations. Possible explanations for the results are discussed.
Analysis of thermal dependence on the germination of braquiarão seeds using the thermal time model
Keywords: Degrees-day; Temperature; Urochloa brizantha